Analysis of Quality of Service on Internet Networks Using the Burst Method - Fariz, Muhammad; Arifudin, Riza (Scientific Journal of Informatics, 2021)
The purpose of this research is to make comparisons on the internet network using the application of the Burst method and processed with Quality of Service analysis in which there are parameters of throughput, delay, and jitter. This analysis was carried out because there was a problem with a slow internet network. This happens because there is no configured bandwidth management on the Microtic router and also the unequal distribution of bandwidth when more and more bandwidth users. Burst is one of the bandwidth management methods available on the Microtic router. This study focuses on the implementation of Burst which is applied to one client2 and will be compared with client1 without the application of Burst. Quality of Service analysis is performed to test the parameters of throughput, delay, and jitter on each of the internet networks. After this test is complete, it shows that the results of using the Burst method as a bandwidth regulator, internet network access can be controlled and each client gets the bandwidth evenly as needed. The work result using Burst is more optimal than performance without using Burst. By using Burst the number of packets lost and failed transactions is reduced by more than 70%.